2006
DOI: 10.1093/jat/30.7.449
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Drug-Facilitated Sexual Assault Using Aromatic Solvents

Abstract: This report documents a case of drug-facilitated sexual assault (DFSA) under the influence of solvents. The victim was a 13-year-old female. Upon contact with law enforcement, she was still confused and could hardly explain the facts. She told authorities that she had been kidnapped 4 h previously when two individuals with covered faces put a cloth soaked in a solvent over her mouth. She spent a few hours in a room, during which she lost consciousness. The girl awakened semi-nude in the street with memory loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Similarly, the offender in the case report by Gaillard et al was speculated to have procured the chloroform from his company, since a 2.5-liter chloroform bottle was found opened at his workplace [ 16 ]. The two remaining studies included the use of aromatic hydrocarbons; the case report by Martínez et al refers to the use of a combination of toluene, benzene, xylene, diazepam, and nordiazepam [ 12 ], while toluene alone was used in a single case of an alleged sexual assault found in the forensic service Northern Ireland (FSNI) database in the study reported by Hall et al [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, the offender in the case report by Gaillard et al was speculated to have procured the chloroform from his company, since a 2.5-liter chloroform bottle was found opened at his workplace [ 16 ]. The two remaining studies included the use of aromatic hydrocarbons; the case report by Martínez et al refers to the use of a combination of toluene, benzene, xylene, diazepam, and nordiazepam [ 12 ], while toluene alone was used in a single case of an alleged sexual assault found in the forensic service Northern Ireland (FSNI) database in the study reported by Hall et al [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…The identities of the offenders in the remaining three studies were unknown. The case reported by Martínez et al only mentions two individuals with their faces covered [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Postmortem ethanol concentrations were determined in pericardial fluid and bone marrow aspirate by HS-GC/ MS (340). Aromatic solvents detected in the blood of a drugfacilitated sexual assault victim were detected using GC-FID and GC/MS in full scan mode after liquid-liquid extraction (341). The precision of breath alcohol testing in the field using the Intoxilyzer 5000C and the effect of truncation has been studied (342).…”
Section: Drugs and Poisonsmentioning
confidence: 99%